A new species of the Genus Bathyaulax Szépligeti from India (Hymenoptera: Braconidae). - Zaka-ur-Rab, Md. (Contributions to Entomology = Beiträge zur Entomologie, 1963)
The author describes a new species of the Braconid genus Bathyaulax from India. Nomenclatural Actsalami Zaka-ur-Rab, 1963 (Bathyaulax), spec. n.